2004
DOI: 10.1158/1078-0432.ccr-04-0183
|View full text |Cite
|
Sign up to set email alerts
|

Altered Expression of Metastasis-Associated and Regulatory Molecules in Effusions from Breast Cancer Patients

Abstract: Purpose: The aim of this study was to characterize phenotypic alterations along the progression of breast carcinoma from primary tumor to pleural effusion through analysis of the expression of proteases, laminin receptors (LRs), and transcription factors involved in invasion and metastasis.Experimental Design: The material studied consisted of 60 malignant pleural effusions from breast cancer patients and 68 corresponding solid tumors (37 primary and 31 metastatic tumors). Expression of matrix metalloproteinas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
62
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 68 publications
(68 citation statements)
references
References 61 publications
(48 reference statements)
5
62
1
Order By: Relevance
“…Pleural effusion CTLs served as surrogates for lung TILs since it has been reported that these CTLs have experienced a similar microenvironment as that of tumors and display similar phenotypes as those of TILs. [27][28] Indeed, our functional analysis showed that, in comparison to CTLs collected from PBMCs, CTLs from the pleural effusion of NSCLC cancer patients exhibited a deficiency in granzyme B production (Fig. S1).…”
Section: Resultsmentioning
confidence: 93%
See 4 more Smart Citations
“…Pleural effusion CTLs served as surrogates for lung TILs since it has been reported that these CTLs have experienced a similar microenvironment as that of tumors and display similar phenotypes as those of TILs. [27][28] Indeed, our functional analysis showed that, in comparison to CTLs collected from PBMCs, CTLs from the pleural effusion of NSCLC cancer patients exhibited a deficiency in granzyme B production (Fig. S1).…”
Section: Resultsmentioning
confidence: 93%
“…It has been shown by others that the restricted glucose concentration in the TME upregulates miR-26a. 27 We examined whether other factors within the TME could also have such an impact. To evaluate the role of factors directly produced by the tumor cell, we stimulated CD8 C T cells in the presence of lyophilized supernatant from 3T3 cell or tumor cell conditioned media (CM).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations